Killer view [large type] - Johansen, Roy (Johansen, Iris. Kendra Michaels series, 2022)
"Kendra Michaels, blind before gaining her sight via a revolutionary surgical procedure, offers her razor-sharp senses to assist her friend Jessie Mercado in a baffling case. An army vet and former bodyguard for the rich and famous, Jessie has faced all kinds of danger but one thing the motorcycle-riding private investigator has never encountered before is an incarceration consultant. Preparing wealthy people to go to prison is big business. When Owen Blake of Mamertine Consulting hires Mercado to find his missing partner, their suspect list is filled with recently released white-collar criminals, a few drug kingpins, and a couple of murderers to keep things interesting. As witnesses turn up dead and car chases leave destruction in their wake, Jessie and Kendra learn just how far someone will go to keep the fate of one man hidden. But why? Together they must hunt down the lethal secrets of Blake's company, hell-bent on staying one step ahead of disaster" -- Amazon.com.